Myeloid sarcoma masquerading as central nervous system diffuse large b-cell lymphoma: a case report and literature review - Hu, Wanli; Liu, Yang; Ma, Chengcheng; Gao, Yuexian; Zeng, Pengyun; Chen, Huiling (Frontiers in Oncology, 2026)
This report presents a challenging case of a 52-year-old male with a history of acute myeloid leukemia (AML) with t(8;21)(q22;q22.1)/RUNX1::RUNX1T1 who developed an intracranial mass during hematologic remission. Initial histopathological examination of the resected lesion, due to aberrant expression of B-cell markers (PAX-5, CD79a, c-Myc, Bcl-2), led to a misdiagnosis of diffuse large B-cell lymphoma (DLBCL). Subsequent comprehensive integration of clinical history, repeated bone marrow assessment, cytogenetics, fluorescence in situ hybridization (FISH), and extended immunohistochemistry(IHC) revealed the tumor to be a myeloid sarcoma (MS), representing an extramedullary relapse of his underlying AML. This case underscores the diagnostic pitfalls of MS, particularly within the central nervous system (CNS), and highlights the critical importance of considering MS in patients with a history of AML, especially those with genetic profiles predisposing to extramedullary disease, even when pathology initially suggests lymphoma.